2009
DOI: 10.2298/jsc0902103h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, reactions and biological activity of 3-arylidene-5-(4-methylphenyl)-2(3H)-furanones?

Abstract: 3-Arylidene-5-(4-methylphenyl)-2(3H)-furanones 2a-m were prepared from 3-(4-methyl-benzoyl)propanoic acid 1 and several aromatic aldehydes. Some of the selected furanones were reacted with ammonia gas and benzylamine to give corresponding 3-arylidene-1,3-dihydro-5-(4-methylphenyl)-2H-pyrrol-2-ones 3a-h and 3-arylidene-1-benzyl-1,3-dihydro-5-(4-methylphenyl)-2H--pyrrol-2-ones 4a-f, respectively, which were characterized on the basis of IR, 1 H-NMR, mass spectral data and elemental analysis results. These compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Pyrrolone considered as an important nucleus with variable biological activities including antibacterial [72], antiinflamatory [72], analgesic, antimycobacterial [73], antidepressant [74], antiviral [75] and antitumor activities [76]. (Figure 17)…”
Section: Biological Activity Of Pyrrolonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyrrolone considered as an important nucleus with variable biological activities including antibacterial [72], antiinflamatory [72], analgesic, antimycobacterial [73], antidepressant [74], antiviral [75] and antitumor activities [76]. (Figure 17)…”
Section: Biological Activity Of Pyrrolonesmentioning
confidence: 99%
“…A series of pyrrol-2-one was prepared by A. Husain et al, [72], the anti-inflammatory activity results showed that compound 81 has comparable activity to declofenac. S. Khokra et al, [77] synthesized a series of quinolinylpyrrolone derivatives and tested as anti-inflammatory agents using carrageenan induced paw edema.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…These heterocycles acquired an obvious medicinal interest as antimicrobial [22][23][24] , antiviral [25][26][27] , antimycobacterial 28,29 , and anti-cancer agents [30][31][32] . Literature is enriched with different 2-furanones subjected to ring opening to form 2-pyrrolone, pyridazinone, and oxadiazole derivatives, all have high activity as anti-inflammatory 24,[33][34][35][36][37][38][39][40][41] . As shown in Figure 1, 2-furanone derivatives Ia-c were reported to exhibit comparable anti-inflammatory activity to that of diclofenac 33,35,36 , while 2-pyrrolone derivatives II, IIIa-b, and IV were reported to have comparable anti-inflammatory activity to that of indomethacin, ibuprofen, and diclofenac, respectively 24,[34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…2-Furanones; well-known heterocyclic derivatives; had attracted a great attention during the last decade due to facile ring opening and conversion to other heterocycles; pyrrolones, pyridazinones, pyrazoles and oxadizoles. These heterocycles acquired an obvious medicinal interest as antimicrobial [6][7][8] , anti-inflammatory [8][9][10][11][12][13][14][15][16] , antimycobacterial 18,19 and anti-cancer agents [20][21][22] Literature is also enriched with furanone derivatives and other heterocyclic and non-heterocyclic compounds derived from them having antiviral activities [23][24][25] , as shown in Figure 1; 2-furanone derivative A showed remarkable activity comparable to that of zanamivir 23 , and furanone derivative B which is reported as potent anti-adenoviral agent. 26 pyridazinone D were reported to have promising antiviral activities against anti-avian influenza virus H5N1 virus.…”
Section: Introductionmentioning
confidence: 99%